Compromised fertility disrupts Peg1 but not Snrpn and Peg3 imprinted methylation acquisition in mouse oocytes - Denomme, Michelle M.; White, Carlee R.; Gillio-Meina, Carolina; MacDonald, William A.; Deroo, Bonnie J.; Kidder, Gerald M.; Mann, Mellissa R. (Frontiers in Genetics, 2012)
Growth and maturation of healthy oocytes within follicles requires bidirectional signaling and intercellular gap junctional communication. Aberrant endocrine signaling and loss of gap junctional communication between the oocyte and granulosa cells leads to compromised folliculogenesis, oocyte maturation and oocyte competency, consequently impairing fertility. Given that oocyte-specific DNA methylation establishment at imprinted genes occurs during this growth phase, we determined whether compromised endocrine signaling and gap junctional communication would disrupt de novo methylation acquisition using ERβ and connexin37 genetic models. To compare mutant oocytes to control oocytes, DNA methylation acquisition was first examined in individual, 20-80 μm control oocytes at three imprinted genes, Snrpn, Peg3 and Peg1. We observed that each gene has its own size-dependent acquisition kinetics, similar to previous studies. To determine whether compromised endocrine signaling and gap junctional communication disrupted de novo methylation acquisition, individual oocytes from Esr2- and Gja4-deficient mice were also assessed for DNA methylation establishment. We observed no aberrant or delayed acquisition of DNA methylation at Snrpn, Peg3 or Peg1 in oocytes from Ers2-deficient females, and no perturbation in Snrpn or Peg3 de novo methylation in oocytes from Gja4-null females. However, Gja4-deficiency resulted in a loss or delay in methylation acquisition at Peg1. One explanation for this difference between the three loci analyzed is the late establishment of DNA methylation at the Peg1 gene. These results indicate that compromised fertility though impaired intercellular communication can lead to imprinting acquisition errors. Further studies are required to determine the effects of subfertility/infertility originating from impaired signaling and intercellular communication during oogenesis on imprint maintenance during preimplantation development.